Efficient red light photo-uncaging of active molecules in water upon assembly into nanoparticles - Carling, Carl-Johan (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
We introduce a means of efficiently photo-uncaging active compounds from amino-1,4-benzoquinone in aqueous environments. Aqueous photochemistry of this photocage with one-photon red light is typically not efficient unless the photocaged molecules are allowed to assemble into nanoparticles. A variety of biologically active molecules were functionalized with the photocage and subsequently formulated into water-dispersible nanoparticles. Red light irradiation through various mammalian tissues achieved efficient photo-uncaging. Co-encapsulation of NIR fluorescent dyes and subsequent photomodulation provides a NIR fluorescent tool to assess both particle location and successful photorelease.